Pemberian Rebusan Daun Salam Pada Lansia dengan Asam Urat di Griya Lansia Jannati Kota Gorontalo - Sri Wulandari; Hamna Vonny Lasanuddin; Nur Uyun I. Biahimo; Andi Nuraina Sudirman (Jurnal Ventilator, 2023)
In the elderly there is a deterioration of cells due to the aging process which can result in organ weakness, physical deterioration, the onset of various diseases such as increased uric acid levels. Another treatment that can be used to overcome increased uric acid levels is with herbal remedies, one of which uses bay leaves, but there are still many elderly who have not used bay leaf decoction to lower uric acid. The purpose of this study was to identify the effect of bay leaf decoction on reducing uric acid in the elderly in the Griya Lansia Janati area, Gorontalo Province. Pre-experimental research method with one group pre post test design, samples of 5 people who meet the sample criteria, the instrument used is easy touch GCU to measure uric acid levels and the data analysis used is univariate analysis by describing differences in uric acid levels for three days. The research findings obtained before being given bay leaf decoction in the results of uric acid in the five clients were, in client 1 uric acid 7.3 mg / dl, in client 2 uric acid 7.1 mg / dl and client 3 uric acid 7.4 mg / dl, client 4 uric acid 8 mg / dl, client 5 uric acid 7.9 mg / dl. The average patient has gout. After the intervention of giving bay leaf water decoction for 4 consecutive days, the results were obtained in client 1 there was a decrease with uric acid 5.3 mg / dl, in client 2 there was a decrease with uric acid mg / dl, client 3 also had a decrease in uric acid 5.2 mg / dl, client 4 decreased uric acid 6 mg / dl, and client 5 decreased uric acid to 5.8 mg / dl. The implication of this research is that the institution can facilitate the use of bay leaf herbal medicine in the elderly in lowering uric acid levels so that this therapy can be continued.